Improving Outcomes of Chemotherapy: Established and Novel Options for Myeloprotection in the COVID-19 Era - Lyman, Gary H.; Kuderer, Nicole M.; Aapro, Matti (Frontiers in Oncology, 2021)
Chemotherapy-induced damage of hematopoietic stem and progenitor cells (HPSCs) often results in myelosuppression that adversely affects patient health and quality of life. Currently, chemotherapy-induced myelosuppression is managed with chemotherapy dose delays/reductions and lineage-specific supportive care interventions, such as hematopoietic growth factors and blood transfusions. However, the COVID-19 pandemic has created additional challenges for the optimal management of myelosuppression. In this review, we discuss the impact of this side effect on patients treated with myelosuppressive chemotherapy, with a focus on the prevention of myelosuppression in the COVID-19 era. During the COVID 19 pandemic, short-term recommendations on the use of supportive care interventions have been issued with the aim of minimizing the risk of infection, reducing the need for hospitalization, and preserving limited blood supplies. Recently, trilaciclib, an intravenous cyclin-dependent kinase 4 and 6 inhibitor, was approved to decrease the incidence of myelosuppression in adult patients when administered prior to platinum/etoposide-containing or topotecan-containing chemotherapy for extensive-stage small cell lung cancer (ES-SCLC). Approval was based on data from three phase 2 placebo-controlled clinical studies in patients with ES-SCLC, showing that administering trilaciclib prior to chemotherapy significantly reduced multilineage myelosuppression, with patients receiving trilaciclib having fewer chemotherapy dose delays/reductions and myelosuppression/sepsis-related hospitalizations, and less need for supportive care interventions, compared with patients receiving placebo. Several other novel agents are currently in clinical development for the prevention or treatment of multilineage or single-lineage myelosuppression in patients with various tumor types. The availability of treatments that could enable patients to maintain standard-of-care chemotherapy regimens without the need for additional interventions would be valuable to physicians, patients, and health systems.